1999
DOI: 10.1097/00003246-199904000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline improves bacterial clearance during hemorrhage and endotoxemia

Abstract: Hemorrhage and endotoxemia induce impaired bacterial clearance from blood and tissue. Treatment with PTX may reduce the risk of bacterial infections by attenuating bacterial colonization of organs in states of hemorrhage and endotoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…29 Animal studies have shown that PTX decreases bacterial translocation and tissue damage in a murine hemorrhage model 30 and significantly reduces lung and kidney bacterial colonization. 31 In a chronic endotoxemia model, PTX significantly reduced lung injury and ICAM-1 expression compared with LPS-treated animals. 32 PTX also downregulates PMN activation [33][34][35] and prevents endotoxin-induced PMN degranulation.…”
mentioning
confidence: 96%
“…29 Animal studies have shown that PTX decreases bacterial translocation and tissue damage in a murine hemorrhage model 30 and significantly reduces lung and kidney bacterial colonization. 31 In a chronic endotoxemia model, PTX significantly reduced lung injury and ICAM-1 expression compared with LPS-treated animals. 32 PTX also downregulates PMN activation [33][34][35] and prevents endotoxin-induced PMN degranulation.…”
mentioning
confidence: 96%
“…Pentoxifylline also inhibits the production of TNF- α by endotoxin-stimulated monocytes/macrophages at the transcriptional level and is effective in reducing serum TNF- α level in mice with endotoxic shock [40], so pentoxifylline as anti-TNF- α agent could decrease bacterial translocation as previously mentioned by Goldman and coworkers [28]. Heller and coworkers [41] have shown that pentoxifylline improves bacterial clearance during hemorrhage and endotoxemia and these authors suggested that pentoxifylline could reduce the risk of bacterial infections by attenuating bacterial colonization of organs. Further investigations showed that pentoxifylline potentially affects endotoxin-induced release of TNF- α which plays an important role in superantigen-mediated shock [18].…”
Section: Discussionmentioning
confidence: 99%
“…This complex pathopysiology is likely to be multifactorial, involving improved host defense responses, decreased inflammatory cytokine release, enhanced cardiac output, organ perfusion, and organ function [25]. This beneficial effect of pentoxifylline may be due to the downregulation of tumor necrosis factor and interleukin-6 [26,27]. Moreover, it has been demonstrated that pentoxifylline inhibits the production of oxygen radicals, the release of lysosomal enzymes, and the formation of thromboxane A 2 .…”
Section: Discussionmentioning
confidence: 99%
“…By preventing the expression of adhesion molecules on the surface of polymorphonuclear granulocytes, reduced adherence on endothelial cells was shown after pentoxifylline [28,29]. An important pathomechanism in the progression of sepsis following hemorrhage is an impairment of the microcirculation resulting in hypoxic tissue injury [27]. Studies show that pentoxifylline treatment after hemorrhagic shock significantly improves tissue oxygenation and survival rate [9,25].…”
Section: Discussionmentioning
confidence: 99%